2009
DOI: 10.1186/1471-2164-10-s2-s10
|View full text |Cite
|
Sign up to set email alerts
|

The value of avian genomics to the conservation of wildlife

Abstract: BackgroundGenomic studies in non-domestic avian models, such as the California condor and white-throated sparrow, can lead to more comprehensive conservation plans and provide clues for understanding mechanisms affecting genetic variation, adaptation and evolution.Developing genomic tools and resources including genomic libraries and a genetic map of the California condor is a prerequisite for identification of candidate loci for a heritable embryonic lethal condition. The white-throated sparrow exhibits a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
87
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 78 publications
2
87
2
Order By: Relevance
“…Similarly, a chromosomal inversion and fusion event in the black muntjac within the past 0.5 million years also bears an imprint of accumulated mutation on the neo-Y chromosome (Zhou et al, 2008). In marked contrast to these studies, the ZAL2 m chromosome, which is estimated to have split from ZAL2 two million years ago, does not show significant signs of genetic degeneration (Thomas et al, 2008;Romanov et al, 2009;Huynh et al, 2011). What might underlie the differences between these cases?…”
contrasting
confidence: 41%
See 2 more Smart Citations
“…Similarly, a chromosomal inversion and fusion event in the black muntjac within the past 0.5 million years also bears an imprint of accumulated mutation on the neo-Y chromosome (Zhou et al, 2008). In marked contrast to these studies, the ZAL2 m chromosome, which is estimated to have split from ZAL2 two million years ago, does not show significant signs of genetic degeneration (Thomas et al, 2008;Romanov et al, 2009;Huynh et al, 2011). What might underlie the differences between these cases?…”
contrasting
confidence: 41%
“…Indeed, the extent of sequence divergence and LD between the ZAL2 forms, revealing the suppression of recombination and their long-term coexistence, suggests that both functional haplotypes are actively maintained, and it was suggested that they might encode coadapted combinations of multiple traits (Falls and Kopachena, 1994;Romanov et al, 2009)-a form of giant supergene combining behavioural as well as plumage variation (Mather, 1950;Clarke et al, 1968;Joron et al, 2006). One remarkable finding is indeed the sheer number of genes locked into very large non-recombining units maintained by balancing selection.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…First, genomics is revolutionizing all aspects of biology, and will play an important role in the conservation of wildlife (Romanov et al, 2009). Soon it may be possible to perform metagenomic analyses of whole forest ecosystems, to assess the effects of deforestation on the spread of EIDs.…”
Section: Deforestation and Avian Diseasementioning
confidence: 99%
“…R. N. M. Sehgal Future studies of the disease ecology of deforestation will take advantage of several technologies that will accelerate the research and increase scientific understanding. First, genomics is revolutionizing all aspects of biology, and will play an important role in the conservation of wildlife (Romanov et al, 2009). Soon it may be possible to perform metagenomic analyses of whole forest ecosystems, to assess the effects of deforestation on the spread of EIDs.…”
Section: General Conclusion and Future Directionsmentioning
confidence: 99%